Children and adolescents' neural response to emotional faces and voices: Age-related changes in common regions of activation. (1st November 2020) - Morningstar, M.; Mattson, W.I.; Singer, S.; Venticinque, J.S.; Nelson, E.E.
ABSTRACT: The perception of facial and vocal emotional expressions engages overlapping regions of the brain. However, at a behavioral level, the ability to recognize the intended emotion in both types of nonverbal cues follows a divergent developmental trajectory throughout childhood and adolescence. The current study a) identified regions of common neural activation to facial and vocal stimuli in 8- to 19-year-old typically-developing adolescents, and b) examined age-related changes in blood-oxygen-level dependent (BOLD) response within these areas. Both modalities elicited activation in an overlapping network of subcortical regions (insula, thalamus, dorsal striatum), visual-motor association areas, prefrontal regions (inferior frontal cortex, dorsomedial prefrontal cortex), and the right superior temporal gyrus. Within these regions, increased age was associated with greater frontal activation to voices, but not faces. Results suggest that processing facial and vocal stimuli elicits activation in common areas of the brain in adolescents, but that age-related changes in response within these regions may vary by modality.